2017
DOI: 10.1158/0008-5472.can-17-0688
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Whole Genome Sequencing of Circulating Tumor Cells Enables Personalized Combination Therapy of Metastatic Cancer

Abstract: Much effort has been dedicated to developing circulating tumor cells (CTC) as a noninvasive cancer biopsy, but with limited success as yet. In this study, we combine a method for isolation of highly pure CTCs using immunomagnetic enrichment/fluorescence-activated cell sorting with advanced whole genome sequencing (WGS), based on long fragment read technology, to illustrate the utility of an accurate, comprehensive, phased, and quantitative genomic analysis platform for CTCs. Whole genomes of 34 CTCs from a pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 48 publications
(60 reference statements)
2
45
0
Order By: Relevance
“…Previous studies have demonstrated the robustness of the IE/FACS method for detection and isolation of highly pure CTCs (>90%), 8,9 and downstream molecular analyses have confirmed the malignant nature of IE/FACS-isolated CTCs. 810 …”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Previous studies have demonstrated the robustness of the IE/FACS method for detection and isolation of highly pure CTCs (>90%), 8,9 and downstream molecular analyses have confirmed the malignant nature of IE/FACS-isolated CTCs. 810 …”
Section: Introductionmentioning
confidence: 72%
“…1 Our group has used EPCAM-based immunomagnetic enrichment and fluorescence-activated cell sorting (IE/FACS) for detection and isolation of circulating tumor cells (CTC) from blood of cancer patients. 8,9 This method involves an initial IE step using magnetic beads coated with monoclonal antibody to EPCAM, followed by FACS to detect and purify CTCs away from blood cells. Previous studies have demonstrated the robustness of the IE/FACS method for detection and isolation of highly pure CTCs (>90%), 8,9 and downstream molecular analyses have confirmed the malignant nature of IE/FACS-isolated CTCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somatic mutations on driver genes in various cancers have been identified [43] and the statistical data will be applied on diagnosis or even on the prediction of cancer risks and incidences [44]. Very recently, it was proposed that analysis of WGS data from circulating tumor cells could be applied for personalized therapy for malignant cancer [45]. Importantly, mutations in 5′-upstream region of the human TERT gene are frequently identified in melanoma [46,47].…”
Section: Transcription Disorders and Human Diseasesmentioning
confidence: 99%
“…Intra-tumor heterogeneity promotes therapeutic resistance through clonal replacement, whereas cancer cell plasticity promotes recurrence through the reactivation of dormant cancer stem cells [31]. A more comprehensive molecular view of cancer is necessary to enable the precise selection of combinatorial targeted therapies for tumor elimination with minimal side effects [32]. Therapeutic resistance to RTK inhibitors is classified into innate resistance, owing to the insufficient activation of the targeted RTK, the aberrant activation of other RTKs that bypass the targeted therapy, or canonical WNT ligand-dependent β-catenin signaling activation, and acquired resistance, owing to secondary mutations in the targeted RTK [23,[33][34][35][36].…”
Section: Functional Proteomics For Personalized Medicinementioning
confidence: 99%